2020
DOI: 10.3390/ijerph17082721
|View full text |Cite
|
Sign up to set email alerts
|

Active Commuting and Physical Fitness: A Systematic Review

Abstract: Physical fitness (PF) is considered an excellent biomarker of health. One possible strategy to improve PF levels is active commuting. This review, performed accordingly to the Preferred Reporting Items for Systematic Reviews guidelines includes scientific articles published in peer-reviewed journals up to December 2019 that aim at examining the relationship between active travel/commuting and PF. The search was performed in three databases (PubMed, Scopus, and Web of Science). Sixteen studies were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 43 publications
1
59
0
5
Order By: Relevance
“…Our results provide relevant information about boys who actively commute to school, since they are more likely to improve their CRF than those who passively commute. However, a recent systematic review 12 suggested that among younger ages, active commuting by cycling is inconsistently related to PF. According to Voss and Sandercock, 39 girls and boys who regularly walked to school were fitter and significantly more likely to be categorised as fit compared with passive commuters.…”
Section: Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide relevant information about boys who actively commute to school, since they are more likely to improve their CRF than those who passively commute. However, a recent systematic review 12 suggested that among younger ages, active commuting by cycling is inconsistently related to PF. According to Voss and Sandercock, 39 girls and boys who regularly walked to school were fitter and significantly more likely to be categorised as fit compared with passive commuters.…”
Section: Peer Reviewmentioning
confidence: 99%
“…11 However, a recent systematic review showed that active commuting is inconsistently related to PF. 12 A cross-sectional study of 1012 adolescents from six secondary education centres in Andalusia analysed the association of the average daily time in ACS with indicators of psychological health in adolescents. The study observed that adolescents who spent more than 15 min daily on active commuting had higher levels of subjective happiness and psychological wellbeing, although as a main limitation, the study did not control for the level of general PA. 13 Therefore, greater participation in ACS could contribute to improved health by increasing physical wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of the growing body of literature in the field strongly support a positive relationship between active school transport (AST) and levels of physical activity [ 9 , 10 ]. Positive associations have also been found between cycling to and from school and cardiovascular fitness [ 9 , 10 , 11 , 12 ]. A relationship between AST and body composition indicators is less clear [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These dissimilarities might take part to differences between countries around the world in prevalence of ACS among children and adolescents showed in the current study and other studies 13,20,41‐43 . Therefore, interventions aiming to increase higher rates of ACS among Spanish children and adolescents are necessary from a public health perspective to obtain all the physical, social, and mental benefits of this mode of commuting 6,9,10 …”
Section: Discussionmentioning
confidence: 68%
“…Importantly, ACS is also associated with numerous health benefits for children and adolescents, including higher physical activity levels, 5,6 reduced risk of development of metabolic diseases, 7 and greater interpersonal relationships 8,9 and independent mobility 10 . It also provides environmental and economic benefits 11 …”
Section: Introductionmentioning
confidence: 99%